Prescription patterns of analgesics for oral conditions in india - Analysis of large medical audit data of outpatients in India's private healthcare sector - Saif Sayeed; Manu Raj Mathur; Vijay Kumar Mishra; Deepti Nagrath; Richard G Watt (Wolters Kluwer Medknow Publications, 2023)
Background: Analgesic use needs to be regulated due to its adverse effects. This study aimed to analyse the change in prescription rates and patterns of the analgesics prescribed for various oral conditions and to analyse their trends across different age groups and gender to promote rational prescription of drugs and eventually influence regulatory policies. Methods: Secondary analysis was conducted on medical audit data collected from the private health sector in India. The prescription rate per 1000 persons per year was calculated from May 2013 to April 2016 using the mean projected population (PP) of India. Cross-tabulations were conducted to analyse the prescription rate and their changes across different age groups, gender and oral conditions. Findings: The mean analgesic prescription rate was highest among the 20-40 age group, and the highest increase was noted in 'non-steroidal anti-inflammatory drug (NSAID) combinations' (3.56 per 1000 persons per year) from May 2013 to April 2016. The 'NSAID combinations' group was also the most prescribed medication across all the oral conditions, with 'diseases of hard tissues' having the highest prescription rate (41.4 and 45.6 per 1000 persons per year, respectively, for 2013-14 and 2015-16). Interpretation: The results indicate an overall increase in the analgesic prescription rate, especially 'NSAID combinations' for each dental disease and age group, a finding that is hard to explain. Due to the lack of prescription guidelines in India, it is difficult to assess whether these analgesics were prescribed rationally or not.